Thyroid Hormone Increases TGF-β1 in Cardiomyocytes Cultures Independently of Angiotensin II Type 1 and Type 2 Receptors - Gabriela Placoná Diniz; Marcela Sorelli Carneiro-Ramos; Maria Luiza Morais Barreto-Chaves (International Journal of Endocrinology)
TH-induced cardiac hypertrophy in vivo is accompanied by increased cardiac Transforming Growth Factor-β1 (TGF-β1) levels, which is mediated by Angiotensin II type 1 receptors (AT1R) and type 2 receptors (AT2R). However, the possible involvement of this factor in TH-induced cardiac hypertrophy is unknown. In this study we evaluated whether TH is able to modulate TGF-β1 in isolated cardiac, as well as the possible contribution of AT1R and AT2R in this response. The cardiac fibroblasts treated with T3 did not show alteration on TGF-β1 expression. However, cardiomyocytes treated with T3 presented an increase in TGF-β1 expression, as well as an increase in protein synthesis. The AT1R blockade prevented the T3-induced cardiomyocyte hypertrophy, while the AT2R blockage attenuated this response. The T3-induced increase on TGF-β1 expression in cardiomyocytes was not changed by the use of AT1R and AT2R blockers. These results indicate that Angiotensin II receptors are not implicated in T3-induced increase on TGF-β expression and suggest that the trophic effects exerted by T3 on cardiomyocytes are not dependent on the higher TGF-β1 levels, since the AT1R and AT2R blockers were able to attenuate the T3-induced cardiomyocyte hypertrophy but were not able to attenuate the increase on TGF-β1 levels promoted by T3.